Relationship between plankton dynamics and growth of the long-lived clam Arctica islandica on the Faroe shelf - Matras, Una; Salter, Ian; Larsen, Karin Margretha H.; Gaard, Eilif; Steingrund, Petur (Frontiers in Marine Science, 2022)
Marine ecosystem dynamics can vary on timescales ranging from months to centuries, but many observational data are limited to just a few decades. The bivalve Arctica islandica may live up to five centuries depositing annual growth increments in its shells which can serve as an indicator for ecosystem productivity. In the present study, 154 specimens of A. islandica were collected on the Faroe Shelf and standardised annual growth increments for 143 of them – 44 from coastal stations and 99 from shelf stations – were compared with climatic, oceanographic and biological variables. A. islandica growth from coastal and shelf stations was not correlated with basin-scale climate indices (the AMO index, the NAO index, the AO index or the subpolar gyre index) or, more locally, with windspeed or sea surface temperature on the Faroe Shelf. For the shelf stations there was a significant negative correlation between A. islandica growth and the volume transport of the Faroe Current flowing just north of Faroe Islands (r = -0.62). There was a weak nonsignificant positive correlation with an index of primary production on the Faroe Shelf (r = 0.31) and a strong negative correlation with a zooplankton biomass index in mid-summer (r = -0.76). There was also a strong positive correlation between A. islandica growth and the biomass of the bottom-feeding fish species Melanogrammus aeglefinus two years later (r = 0.62). These results seem to suggest that A. islandica growth may represent the amount of fresh phytoplankton that reaches the near-bottom water layers and could probably be regarded as a proxy for the strength of pelagic-benthic coupling that is modulated through phytoplankton-zooplankton interactions in the overlying water. Our results highlight the potential for A. islandica to serve as a long-term proxy for linking variability in pelagic ecosystem dynamics to demersal fish stocks.